Regulatory Dendritic Cell Infusion Prolongs Kidney Allograft Survival in Nonhuman Primates. Issue 8 (11th June 2013) - Ezzelarab, M. B.; Zahorchak, A. F.; Lu, L.; Morelli, A. E.; Chalasani, G.; Demetris, A. J.; Lakkis, F. G.; Wijkstrom, M.; Murase, N.; Humar, A.; Shapiro, R.; Cooper, D. K. C.; et al.
Abstract: We examined the influence of regulatory dendritic cells (DCreg), generated from cytokine‐mobilized donor blood monocytes in vitamin D3 and IL‐10, on renal allograft survival in a clinically relevant rhesus macaque model. DCreg expressed low MHC class II and costimulatory molecules, but comparatively high levels of programmed death ligand‐1 (B7‐H1), and were resistant to pro‐inflammatory cytokine‐induced maturation. They were infused intravenously (3.5–10 × 10 6 /kg), together with the B7‐CD28 costimulation blocking agent CTLA4Ig, 7 days before renal transplantation. CTLA4Ig was given for up to 8 weeks and rapamycin, started on Day −2, was maintained with tapering of blood levels until full withdrawal at 6 months. Median graft survival time was 39.5 days in control monkeys (no DC infusion; n = 6) and 113.5 days (p < 0.05) in DCreg‐treated animals (n = 6). No adverse events were associated with DCreg infusion, and there was no evidence of induction of host sensitization based on circulating donor‐specific alloantibody levels. Immunologic monitoring also revealed regulation of donor‐reactive memory CD95 + T cells and reduced memory/regulatory T cell ratios in DCreg‐treated monkeys compared with controls. Termination allograft histology showed moderate combined T cell‐ and Ab‐mediated rejection in both groups. These findings justify further preclinical evaluation of DCreg therapy and their therapeutic potential in organ transplantation. Abstract : Infusion of regulatory dendritic cells, in combination with costimulation blockade and rapamycin, prolongs renal allograft survival and regulates donor‐specific memory T cells in a clinically relevant nonhuman primate model.